Flipbook Media Improves Elementary Students’ Reading Literacy in Fairy Tales: Media Flipbook Meningkatkan Literasi Membaca Dongeng Siswa SD - Yolanita, Clarissa; Sarimanah, Eri; Yani, Indri (Indonesian Journal of Innovation Studies, 2025)
General Background: Reading literacy is a critical competency for elementary students, especially in the context of Indonesia’s low international reading scores. Specific Background: Despite the integration of literacy programs, traditional learning media have failed to maintain students’ interest and improve comprehension. Knowledge Gap: Limited interactive and engaging digital learning tools tailored to Indonesian cultural values hinder literacy development. Aims: This study aims to develop and evaluate a digital flipbook learning medium using fairy tales to improve reading literacy among third-grade students. Results: Implementing the ADDIE model, the flipbook was validated by media, language, and content experts with “very good” ratings, and applied to 38 students at SDN Panaragan 3. Significant literacy improvement was recorded in 89.5% of participants (N-Gain = 0.74, categorized as “High”), supported by Wilcoxon test and effect size analysis (58%). Novelty: The innovation lies in integrating Canva and Simplebooklet for culturally embedded storytelling and interactive multimedia features to enhance engagement and comprehension. Implications: Flipbooks show promise as scalable, user-friendly digital media for literacy instruction in primary education and suggest pathways for future research in digital pedagogy rooted in local context.Highlight : Flipbook media significantly improved reading literacy, shown by a 0.74 N-Gain score (high category). The ADDIE model guided systematic development, from needs analysis to evaluation. Validation by experts confirmed the flipbook's quality in design, language, and content. Keywords : Flipbook, Reading Literacy, Elementary Students, Fairy Tale, ADDIE Model